IMPLEMENTATION OF THE JUDGE'S DETERMINATION REGARDING MARRIAGE DISPENSATION BASED ON MARRIAGE LAW IN INDONESIA - Risdalina Siregar, SH, MH; Indra Kumalasari M; Putri Habibah Siregar (Jurnal Ilmiah Advokasi, 2024)
This type of research is Empirical Juridical research. namely a research method that implements normative legal provisions (laws) and is described in facts in the field. The results of the research show that the Rantauprapat Religious Court Judge's consideration in granting or rejecting a request for marriage dispensation is based on the evidence submitted by the applicant. However, if the evidence submitted is complete and the reasons are urgent, the judge will grant the request for a marriage dispensation and then the applicant takes the marriage dispensation decision to the local Religious Affairs Office (KUA) to carry out the marriage. The results of this research show that the factors and basis for the judge's considerations behind the request for marriage dispensation are that it is urgent because the woman was already pregnant before legally marrying, as stated in article 7 paragraph 2 of Law No. 16 of 2019, and the administrative requirements marriage or other documents explaining the identity and educational status of the child and the identity of the parents/guardians (Article 5 paragraph (2) Perma No. 5 of 2019);Keywords: Determination; Judge; Dispensation, Marriage